Keterlibatan Peran Ayah Sebagai Pendidik Anak Menurut al-Quran (Studi Komparatif: Tafsir Al-Misbah dan Tafsir Mafatih al-Ghaib) - Widya Rosi Juliyanti (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2025)
This study examines the involvement of fathers as educators of their children from the perspective of the Qur’an through a comparative study of Tafsir Al-Misbah by M. Quraish Shihab and Tafsir Mafatih al-Ghaib by Fakhruddin ar-Razi. The main research problems are how both exegetes interpret the father’s role as an educator, what similarities and differences exist, and how their views remain relevant to child education in Indonesia. This research applies a qualitative method with a hermeneutic approach through library research. Primary data were obtained from both tafsir works, supported by secondary sources such as other tafsir, books, and scholarly articles. The findings reveal that Quraish Shihab emphasizes the father’s role as an emotional, communicative, and affectionate guide, while Fakhruddin ar-Razi stresses rationality, theological arguments, and the strengthening of faith. The synthesis of both perspectives results in the concept of “father’s capital,” which covers spiritual, moral, intellectual, and emotional dimensions. The study concludes that the father’s involvement in children’s education is not only significant in the normative religious context but also practical in shaping an Islamic parenting model relevant to contemporary challenges.